THE INFLUENCE OF SOCIAL MEDIA MARKETING ON CONSUMER TRUST IN ALLIANCE FRANCAISE MEDAN THROUGH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE - Nida Nafisa; Beby Karina Fawzeea Sembiring; Erman Munir (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze the influence of Social Media Marketing on Consumer Trust at Alliance Française (AF) Medan with Consumer Satisfaction as an intervening variable. The background of the study is based on pre-survey findings that indicate a gap between AF Medan's social media activities, which were considered quite good by students, and the reality of the decreasing number of students from 2023 to 2025. This study uses a quantitative explanatory approach with a saturated sample of 30 active AF Medan students. Data were collected through a Likert scale questionnaire and analyzed using SEM-PLS and Baron and Kenny mediation tests to examine direct and indirect effects. The results show that Social Media Marketing has a positive and significant effect on Consumer Satisfaction, and Consumer Satisfaction has a significant effect on Consumer Trust. Social Media Marketing was also found to have a direct effect on Consumer Trust. In addition, Consumer Satisfaction was proven to mediate the relationship between Social Media Marketing and Consumer Trust, indicating that an effective digital marketing strategy increases student satisfaction and ultimately strengthens their trust in AF Medan. These findings provide important implications for cultural institutions to strengthen the consistency of digital content, increase interactivity, and ensure the match between digital image and actual service quality to build long-term trust.